A study on factors that influence training effectiveness in organization / Nurizati Izyan Mohd Kasbi and Nasuha Ayuhan - Mohd Kasbi, Nurizati Izyan; Ayuhan, Nasuha (Faculty of Business and Management, 2014)
This study was conducted to study the relationship between factors that influence training effectiveness in organization. The subject area was at Majlis Perbandaran Muar. In order to determine the relationship between the factors and training effectiveness the researcher decided to come out with three type of factors which is training environment, individual characteristics and also work environment. This study involves 123 respondents from any division at Majlis Perbandaran Muar. The result indicates from the finding shows that all elements have significant positive relationship and thus support the hypotheses presented in this research study. More over the most influential factor are individual characteristics where the Pearson’s Correlation value is 0.628. As a conclusion, this research study helps the other researcher to explore the relationship between training effectiveness and the factors that affecting training effectiveness in organization. This study also supported by previous research result.